Between science and art - Martin, Colin (The Lancet (British edition), 2001)
The most striking art exhibit is Breathe, part of a series of works resulting from a continuing, interdisciplinary collaboration between an artist, Rachael Chapman, and Jane Nicklin and Jenny Smale, mycologists at Birkbeck College, London, UK. In making the work, three huge dishes of nutrient-rich agar jelly were left exposed to the atmosphere in and around the Wellcome building. They captured airborne fungal spores, which multiplied to create a disquieting, self-contained world, patterned with microbiological colonies. "A pattern is drawn of the breath city, a breath that has been exhaled by many pairs of lungs; a gulp of air that anyone of us might take is made alarmingly, but beautifully visible," explains Chapman. Also dependent on microbial colonisation is Funge?ia, Serge Negre's series of photographs of the anthropomorphic and zoomorphic patterns created by Aspergillus flavius, which Negre found on the pages of 19th-century books. Unlike the other art works, Breathe and Fungteria are accidental, their random form is reliant on natural growth, rather than upon artistic intervention. By bringing the results of these processes to our attention, the artists are functioning like scientists-although, unlike researchers, they do not try to explain the significance of their findings overtly.